Quantitative analysis of the impact of flue gas recirculation on the efficiency of oxy-coal power plants. (April 2020) - Gopan, Akshay; Verma, Piyush; Yang, Zhiwei; Axelbaum, Richard L.
Highlights: Effect of flue gas recycle on the efficiency of an oxy-combustion plant is explained. Exergy losses are a significantly greater contributor than fan power consumption. Net plant efficiency non-linearly dependent on recycle ratio. Knee in the efficiency vs. recycle ratio exists at approx. 33% recycle. Low recycle is almost as efficient as zero recycle; may work better in practice. Abstract: Oxy-combustion typically consists of burning coal with a combination of oxygen and a large amount of recycled flue gas (60–70%) to obtain a similar heat flux profile to that of air-fired systems. As the cost of electricity from first-generation oxy-combustion is relatively high, several new oxy-combustion process concepts have been proposed in recent years, and within these, the proposed amount of flue gas recycle (FGR) has varied from near-zero to 80%. To better understand the fundamental impact of FGR on the efficiency of oxy-combustion systems, a thermodynamic approach is used herein. Second-law losses associated with flue gas recycle are found to be significant and highly non-linear with recycle ratio. A difference in efficiency of up to 10 %-points can be realized, with a maximum efficiency occurring at zero FGR. Furthermore, due to the non-linear relation of plant efficiency with recycle ratio, processes with low recycle (< ∼33%) experience only a small efficiency penalty, compared to no recycle. Additionally, fan power requirements also scale non-linearly with recycle ratio, resulting in significantly lower FGR fan power requirements for low recycle processes as well. These results suggest that for systems employing cold recycle, FGR should be kept below 33%. Due to the recent interest in developing pressurized oxy-combustion (POC) for efficient, low-cost carbon capture, the impact of flue gas recycle on POC systems is also presented, with a discussion on the valorization strategies for the latent heat of flue gas moisture recovery.